Odpowiedź:
zad. 3
[tex]a)3 {a}^{2} b + 15 {a}^{2} b = 18 {a}^{2} b[/tex]
[tex]b)5xy - 8xy = - 3xy[/tex]
[tex]c) - 12xyz + \frac{1}{2} xyz = - 11 \frac{1}{2} xyz[/tex]
zad. 4
[tex]a)15ax - 3ay + 2ay - 5ax - 12ax + 4xy - 2 = - 2ax - ay + 4xy - 2[/tex]
[tex]b) - {a}^{2} {b}^{2} {c}^{2} + abc - {a}^{2} b {c}^{2} + a {b}^{2} c + {a}^{2} {b}^{2} {c}^{2} + {a}^{2} b {c}^{2} - a {b}^{2} c = abc[/tex]
zad. 5
[tex]ob = (4b - 1) + (2b + 2) + 2a + (3a + 1) = 4b - 1 + 2b + 2 + 2a + 3a + 1 = 2b + 5a + 2[/tex]